Differential effects of patient symptom subtypes on informal hospice caregiver depression. Issue 2 (31st January 2017) - Wilkes, Chelsey M.; Washington, Karla T.; Palmer, William M.; Parker Oliver, Debra; Demiris, George; Craig, Kevin
ABSTRACT: Objective: Researchers sought to determine the extent to which burden related to patients' symptom subtypes could predict informal hospice caregiver depression, and to illustrate the differences between caregivers who experience suicidal ideation and those who do not. Method: Informal caregivers recruited from a not-for-profit community-based hospice agency participated in a cross-sectional survey. Self-report questionnaires assessed caregiver burden associated with patient symptomatology (via a modified version of the Memorial Symptom Assessment Scale–Short Form) and caregiver depressive symptoms, including suicidal ideation (measured by the Patient Health Questionnaire–9). Multiple regressions evaluated the unique predictability of patients' symptom subtypes on caregiver depression. Exploratory analyses examined mean differences of study variables between participants who did and did not endorse suicidal ideation. Results: Caregiver burden related to patients' psychological symptoms accounted for significant variance in caregiver depression scores when controlling for burden related to physical symptoms. Among 229 caregivers ( M age = 61.4 years), 12 reported suicidal ideation, where 6 of the 12 were male, despite male caregivers comprising less than 20% of the total sample. Significance of results: Burden associated with patients' psychological symptoms uniquely contributed to caregiver depression, further highlighting the clinical utility and necessity for hospice providers to address the emotional needs of patients and their caregivers alike. Developing clinical procedures to identify and respond to such needs would not only behoove hospice agencies, but it would likely enhance the caregiving experience holistically, which might be particularly imperative for male caregivers.